Challenges in Screening of Sexually Transmitted Viral Infections of the Female Genital Tract: Where Do we Stand? - A scoping review - Jamshed, Bushra; Javed, Maham; Zaki, Saima; Khalid, Huma; Idrak, Sobia; Naseem, Nadia (Journal of the Pakistan Medical Association, 2022)
Globally more than a million sexually transmitted infections occur daily, and over 53 000 [47,000–60,000] women aged 15 and over were living with human immunodeficiency virus / acquired immunodeficiency syndrome in Pakistan by the year 2020. This situation becomes graver when the sexually transmitted infections exist as co-infections while remaining undiagnosed or under-diagnosed. Additionally, herpetic or papillomavirus lesions are more recurrent, more extensive and have more serious consequences in human immunodeficiency virus-positive patients. Literature shows a dramatic increase in morbidity and mortality due to the occurrence of malignancies in genital co-infections. There is a key concern that every single adolescent female living in Pakistan is at a high risk of acquiring viral sexually transmitted infections along with malignancy of the cervix. —Continue